Sistem Zonasi dalam Perspektif Pendidikan - Asih Pangestuti (Pascasarjana Universitas Jenderal Soedirman, 2021)
This scientific study aims to determine the application of the zoning system from an educational perspective. The research was conducted using qualitative methods. The perspectives raised were the perspectives of students and teachers from favorite and not favorite schools. The results showed that the students 'and teachers' perspectives on the zoning system included: 1) the zoning system equalized access to education services; 2) the zoning system increases the spirit of teaching teachers; 3) the zoning system restricts students from choosing the desired school; 4) the zoning system causes weak students to miss lessons; 5) the zoning system causes smart students to have no challenges to improve achievement; 6) the zoning system increases the teaching load of teachers. The application of the zoning system must always be evaluated and improved in order to realize the quality of education. The implementation of the zoning system must also be accompanied by equal distribution of public schools, school infrastructure, teacher resources, and educational assistance. Schools need to implement strategies in dealing with the zoning system through programs for developing student academic and non-academic potential, developing teacher competencies, and developing school culture.